2007
DOI: 10.1002/ejic.200601024
|View full text |Cite
|
Sign up to set email alerts
|

Insight Into the Intermolecular Factors Responsible for theZ,ZConfiguration of Ar–X–N=S=N–X–Ar (X = S, Se) Derivatives in the Solid State

Abstract: The molecular and crystal structures of three new derivatives of Ph–S–N=S=N–S–Ph (1), with 2,4,6‐(tert‐C4H9)3C6H2 (4), C6F5 (5) and 4‐CF3C6F4 (6) as peripheral rings, respectively, and one new derivative of Ph–Se–N=S=N–Se–Ph (2), with C6F5 (7) as peripheral rings, are reported and discussed in connection with those of the two parent structures 1 and 2 and those of the previously studied derivative of 1 containing 4‐ClC6H4 (3) as peripheral rings. For these seven compounds the Z,Z configuration is the only one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…[29b,29c,44,46a-46c] This system features a notably low IE 1 , low-lying π*-excited states, and enhanced magnetic shielding of the 1 H, 13 C, and 19 F nuclei attached to C5 and C8, i.e., those closest to the heterocycle, probably due to paratropic ring currents in the latter. All these peculiarities can be associated with antiaromaticity.…”
Section: Aromaticity/antiaromaticitymentioning
confidence: 99%
See 2 more Smart Citations
“…[29b,29c,44,46a-46c] This system features a notably low IE 1 , low-lying π*-excited states, and enhanced magnetic shielding of the 1 H, 13 C, and 19 F nuclei attached to C5 and C8, i.e., those closest to the heterocycle, probably due to paratropic ring currents in the latter. All these peculiarities can be associated with antiaromaticity.…”
Section: Aromaticity/antiaromaticitymentioning
confidence: 99%
“…The most interesting feature of the NMR spectra of compounds 1 is the enhanced shielding of the 1 H, 13 C, and 19 F nuclei (for the monofluoro derivatives) attached to C5 and C8 -i.e., those closest to the heterocycle -as compared to those attached to C6 and C7. [23c,29] For 1h, δ( 1 H) is 5.90 and 5.79 for H5 and H8, and 6.63 and 6.79 for H6 and H7, respectively.…”
Section: Multinuclear Nmr Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…packing forces) are the main driving force behind the experimentally observed Z,Z configurations. [7] In this situation, the stabilization of the E,Z isomer in the crystal can be considered as a challenge for the structural and supramolecular chemistry and crystal engineering of chalcogen-nitrogen compounds. One way to address the problem is by affecting the crystal packing through specific intermolecular interactions, [10] which are different from the X···X interactions observed in the crystal lattices of the already studied Z,Z isomers.…”
Section: Introductionmentioning
confidence: 99%
“…both (substituted) hydrocarbon and fluorocarbon groups], only the Z,Z configuration was found in the solid state, while the coexistence of the Z,Z and E,Z isomers was observed by NMR spectroscopy in solution and predicted by quantum chemical calculations in the gas phase. [7] Ph-N=S=N-S-N=S=N-Ph [8] and Ph-S-N=S=N-S-N=S=N-S-Ph [9] possess the E,Z,E,Z and Z,E,Z,Z configurations in the crystal, respectively, whereas the macromolecular (SN) x adopts the ...E,Z,E,Z... configuration. [1] For the Ar-X-N=S=N-X-Ar (X = S, Se) derivatives, it was shown that their configurational preference in the solid state cannot be explained by intramolecular stereoelectronic effects, and that intermolecular factors (i.e.…”
Section: Introductionmentioning
confidence: 99%